Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve for the difference quotient of the given function [tex]\( f(x) = -9x^2 + 6x + 6 \)[/tex] and subsequently simplify it, follow these steps:
1. Define the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = -9x^2 + 6x + 6 \][/tex]
2. Determine [tex]\( f(x + h) \)[/tex] by substituting [tex]\( x + h \)[/tex] into the function:
[tex]\[ f(x + h) = -9(x + h)^2 + 6(x + h) + 6 \][/tex]
[tex]\[ = -9(x^2 + 2xh + h^2) + 6x + 6h + 6 \][/tex]
[tex]\[ = -9x^2 - 18xh - 9h^2 + 6x + 6h + 6 \][/tex]
3. Compute the difference [tex]\( f(x + h) - f(x) \)[/tex]:
[tex]\[ f(x + h) - f(x) = (-9x^2 - 18xh - 9h^2 + 6x + 6h + 6) - (-9x^2 + 6x + 6) \][/tex]
[tex]\[ = -9x^2 - 18xh - 9h^2 + 6x + 6h + 6 + 9x^2 - 6x - 6 \][/tex]
[tex]\[ = -18xh - 9h^2 + 6h \][/tex]
4. Form the difference quotient by dividing by [tex]\( h \)[/tex]:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{-18xh - 9h^2 + 6h}{h} \][/tex]
[tex]\[ = \frac{-18xh}{h} + \frac{-9h^2}{h} + \frac{6h}{h} \][/tex]
[tex]\[ = -18x - 9h + 6 \][/tex]
5. Simplify the expression (since [tex]\( h \neq 0 \)[/tex]):
[tex]\[ \frac{f(x + h) - f(x)}{h} = -18x - 9h + 6 \][/tex]
Therefore, the simplified difference quotient for the function [tex]\( f(x) = -9x^2 + 6x + 6 \)[/tex] is:
[tex]\[ \boxed{-18x - 9h + 6} \][/tex]
1. Define the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = -9x^2 + 6x + 6 \][/tex]
2. Determine [tex]\( f(x + h) \)[/tex] by substituting [tex]\( x + h \)[/tex] into the function:
[tex]\[ f(x + h) = -9(x + h)^2 + 6(x + h) + 6 \][/tex]
[tex]\[ = -9(x^2 + 2xh + h^2) + 6x + 6h + 6 \][/tex]
[tex]\[ = -9x^2 - 18xh - 9h^2 + 6x + 6h + 6 \][/tex]
3. Compute the difference [tex]\( f(x + h) - f(x) \)[/tex]:
[tex]\[ f(x + h) - f(x) = (-9x^2 - 18xh - 9h^2 + 6x + 6h + 6) - (-9x^2 + 6x + 6) \][/tex]
[tex]\[ = -9x^2 - 18xh - 9h^2 + 6x + 6h + 6 + 9x^2 - 6x - 6 \][/tex]
[tex]\[ = -18xh - 9h^2 + 6h \][/tex]
4. Form the difference quotient by dividing by [tex]\( h \)[/tex]:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{-18xh - 9h^2 + 6h}{h} \][/tex]
[tex]\[ = \frac{-18xh}{h} + \frac{-9h^2}{h} + \frac{6h}{h} \][/tex]
[tex]\[ = -18x - 9h + 6 \][/tex]
5. Simplify the expression (since [tex]\( h \neq 0 \)[/tex]):
[tex]\[ \frac{f(x + h) - f(x)}{h} = -18x - 9h + 6 \][/tex]
Therefore, the simplified difference quotient for the function [tex]\( f(x) = -9x^2 + 6x + 6 \)[/tex] is:
[tex]\[ \boxed{-18x - 9h + 6} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.